2006
DOI: 10.1103/physrevb.74.054435
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electronic structure and magnetism ofMn2NiGa: Experiment and density-functional theory calculations

Abstract: Both experimental and theoretical studies have been carried out to study the structure and magnetic properties of Mn 2 NiGa alloys. We have found, instead of forming L2 1 structure where both A and C sites are occupied by Mn atoms, the alloy favor a structure where the C site is occupied by Ni atoms and Mn atoms at A and B sites. The electronic structures of both cubic austenite and tetragonal martensite Mn 2 NiGa were calculated by self-consistent full-potential linearized-augmented plane-wave ͑FP-LAPW͒ metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
66
2
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 174 publications
(82 citation statements)
references
References 39 publications
10
66
2
4
Order By: Relevance
“…In NieMneGa ternary system, two intermetallic compounds, namely Ni 2 MnGa [1,2] and Mn 2 NiGa [3,4], were reported to present in the bcc phase (b) region that covers over a wide range of compositions at high temperature [5]. These two intermetallic compounds all belong to highly ordered L2 1 Heusler structure, but with different atom occupation and space group, as confirmed by experimental and theoretical studies in previous investigations [3,4].…”
Section: Introductionsupporting
confidence: 67%
“…In NieMneGa ternary system, two intermetallic compounds, namely Ni 2 MnGa [1,2] and Mn 2 NiGa [3,4], were reported to present in the bcc phase (b) region that covers over a wide range of compositions at high temperature [5]. These two intermetallic compounds all belong to highly ordered L2 1 Heusler structure, but with different atom occupation and space group, as confirmed by experimental and theoretical studies in previous investigations [3,4].…”
Section: Introductionsupporting
confidence: 67%
“…The desired properties of the materials Mn 3?x Ga can easily be tuned by substitution of elements, i.e., variation of the Mn:Ga ratio. The recently discovered ferrimagnetic shape memory compound Mn 2 NiGa exhibits a record-breaking magnetic-field-induced strain of approximately 21% in its single crystalline form [21,22]. Co 2 -based Heusler compounds often follow the Slater-Pauling rule, which is a signature for their half metallicity.…”
Section: Introductionmentioning
confidence: 99%
“…The austenite phase of Mn excess Ni-Mn-In alloys is known to be ferromagnetic whereas the martensite phase is generally believed to be nonmagnetic (either paramagnetic or antiferromagnetic) [6,8,11], whereas in the Mn excess Ni-Mn-Ga alloys, both the austenite and the martensite phases are reported to be ferrimagnetic [10,[16][17][18]. Using high-resolution synchrotron and laboratory x-ray powder-diffraction (XRD) data, it is shown that the martensite structure can be stabilized by residual stresses over a wide temperature range well above A f in both alloy systems.…”
mentioning
confidence: 99%